SPE California Regional Meeting 1979
DOI: 10.2118/7977-ms
|View full text |Cite
|
Sign up to set email alerts
|

Transient Pressure Behavior Of Naturally Fractured Reservoirs

Abstract: The naturally fractured reservoir model presented by Warren and Root was extended to improve analysis of field data and to account for practical wellbore and reservoir conditions. These conditions include wellbore storage and damage, and constant producing pressure in infinite define pseudo-steady state and pressure in infinite define pseudo-steady state and long time reservoir behavior. Introduction In recent years, numerous models have been propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…De Swaan (1976) also provided solutions for reservoirs in which the matrix blocks are either slabs or spheres. Mavor and Cinco-Ley (1979) and Moench (1984) extended the dual porosity approach to include the effect of skin between the matrix and the fracture system. They showed that the pseudo-steady state assumption used in the transfer function of the Warren and Root's approach can be justified when the effect of skin is pronounced.…”
Section: Dual Continuum Modelsmentioning
confidence: 99%
“…De Swaan (1976) also provided solutions for reservoirs in which the matrix blocks are either slabs or spheres. Mavor and Cinco-Ley (1979) and Moench (1984) extended the dual porosity approach to include the effect of skin between the matrix and the fracture system. They showed that the pseudo-steady state assumption used in the transfer function of the Warren and Root's approach can be justified when the effect of skin is pronounced.…”
Section: Dual Continuum Modelsmentioning
confidence: 99%
“…Long shut-in periods are very helpful in solving this problem and both in Masjid-i-Suleiman (Gibson 1948) and in Amposta Marino fields such periods provided the key to a realistic estimate of the fracture porosity. Mavor et al (1979) discuss the analysis of one well pressure build-up curves of the type used for the Amposta Marino field. The basic principle is the recognition of two parallel, semilog straight lines in the build-up graphs.…”
mentioning
confidence: 99%
“…2). Wellbore storage and skin effects were included in the Warren and Root (1963) types models by Mavor and Cinco-Ley (1979). Fig.…”
Section: February 2014 Spe Reservoir Evaluation and Engineeringmentioning
confidence: 99%